2007
DOI: 10.1111/j.1574-695x.2007.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiadhesive property of microalgal polysaccharide extract on the binding ofHelicobacter pylorito gastric mucin

Abstract: The emergence of antibiotic-resistant Helicobacter pylori is of concern in the treatment of H. pylori-associated gastroduodenal diseases. As the organism was reported to bind gastric mucin, we used porcine gastric mucin as substrate to assess the antiadhesive property of polysaccharides derived from Spirulina (PS), a commercially available microalga, against the binding of H. pylori to gastric mucin. Results show that polysaccharides prevented H. pylori from binding to gastric mucin optimally at pH 2.0, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 24 publications
1
23
0
2
Order By: Relevance
“…Instead, urease activity must be acid–dependent and thus, once in their natural niche, DU strains are better protected against a sudden drop in pH and/or in Ni 2+ concentration which explains their ability to survive under abnormally acidic conditions [34]. Moreover, since urease has also been proposed to play a role in adherence to gastric mucins [37], again in a acid dependent manner [38], higher levels of urease may facilitate the processes of colonization and infection, contributing to the ulcerogenic phenotype of DU strains.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, urease activity must be acid–dependent and thus, once in their natural niche, DU strains are better protected against a sudden drop in pH and/or in Ni 2+ concentration which explains their ability to survive under abnormally acidic conditions [34]. Moreover, since urease has also been proposed to play a role in adherence to gastric mucins [37], again in a acid dependent manner [38], higher levels of urease may facilitate the processes of colonization and infection, contributing to the ulcerogenic phenotype of DU strains.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that laminin is the host receptor of both AlpA and AlpB, and H. pylori deficient in these factors causes more severe inflammation than the isogenic wild-type strain in gerbils (Senkovich et al, 2011). The reason may be that the alpAB locus influences host cell signaling and cytokine production (Odenbreit et al, 2002a,b; Loke et al, 2007; Lu et al, 2007). H. pylori CagL protein is a specialized adhesin that is targeted to the pilus surface, where it binds to and activates integrin alpha5beta1 receptor on gastric epithelial cells through an arginine-glycine-aspartate motif.…”
Section: Adhesinsmentioning
confidence: 99%
“…Furthermore, although the urease and alkyl hydroperoxide reductase (AhpC) located on the surface of H. pylori are not OMPs, these enzymes still have good affinity for stomach mucins because they are components of the membrane (Nilsson et al, 2000). Loke et al (2007) confirmed that both polysaccharides and mucin could bind to AhpC and UreA, so polysaccharides may function as a potential anti-adhesive agent against H. pylori colonization of gastric mucin by competing for mucin-binding sites. This result indirectly indicated the probable role of these two H. pylori proteins in colonization.…”
Section: Adhesinsmentioning
confidence: 99%
“…LecA is a galactosidebinding adhesin that has been shown to contribute to P. aeruginosa biofilm architecture under different environmental conditions (Diggle et al, 2006). Various polysaccharides isolated from plants including okra fruit (Lengsfeld et al, 2004;Wittschier et al, 2007), Aloe vera (Xu et al, 2010), licorice root (Wittschier et al, 2007;2009), ginseng (Lee et al, 2004;2009a), blackcurrant (Wittschier et al, 2007), as well as polysaccharides isolated from the microalga Chlorella and Spirulina (Loke et al, 2007), have been shown to inhibit binding of Helicobacter pylori to gastric cells and mucin in vitro. Spirulina polysaccharides were also shown to inhibit colonization of mice by H. pylori (Loke et al, 2007).…”
Section: Non-bacterial Antibiofilm Polysaccharidesmentioning
confidence: 99%